Endomyocardial Biopsy and Magnetic Resonance Imaging of Acute Myocarditis with Adult-Onset Still's Disease - Yamazoe, Masahiro (Korean Circ J, 2014)
A 36-year-old female with a high-grade fever and epigastric abdominal pain was prescribed antibiotics, but developed hypoxia and dyspnea. An echocardiography revealed diffuse hypokinesis and massive pericardial effusion, after which diagnostic cardiac catheterization and an endomyocardial biopsy (EMB) were peformed to reveal fibrosis and infiltration of inflammation cells composed primarily of neutrophils. Clinical manifestation of a spiking fever, leukocytosis, elevated ferritin levels, skin rash and EMB findings led to a diagnosis of adult-onset Still's disease (AOSD) with acute myocarditis. Pulse therapy of intravenous methylprednisolone was performed for three days, followed by a daily dose of prednisone (60 mg). After a course of steroid therapy for fever and pericardial effusion, and conducting a left ventricular ejection fraction, the patient showed improvement and was discharged asymptomatic within 32 days of admission. This study is the first to report on a case of myocarditis in AOSD diagnosed by neutrophil infiltration in the myocardium.